PENGARUH LINGKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI (Suatu Studi di Kantor Kecamatan Tuminting Kota Manado) - SINADIA, CRISTIN; ROMPAS, SONNY; DENGO, SALMIN (Sam Ratulangi University, 2014)
Abstract : The internal environment is the overall factor in the organization and the activities of theorganization. In the study are two main problems, namely the environmental conditions and the level ofemployee performance in organizations. The study tries to show the influence of the organizationalenvironment on employee performance in Tuminting district, Manado city . This study uses a quantitativeapproach with descriptions and explanations. Data sources or respondents of this study are all employeesof the district office Tuminting, numbering 32 people. Data was collected through a questionnaire andengineering survey using observation techniques. Analysis of the data involved using a simple correlationanalysis technique and simple regression. The results of the data analysis: 1.the environmentalorganization at the district offices in Tuminting is based on the opinions of respondents in the categoriesand are likely to be high or medium.2.Employee performance is likely to be low or medium.3.Theregression coefficient of the variable work environment on employee performance is positive andsignificant and the correlation coefficient of determination is also. Based on the results of data analysis itmay be concluded that the environmental organization, working environment is significantly positive inthe office at Tuminting, Manado city. From the conclusion of the study it is suggested that theorganization’s leaders, in particular the leader of Tuminting district, are able to create conditions of acondusive working environment and stimulate morale of the employees and also the need for concreteefforts of local governments to create the conditions for a better working environment.Keywords : Environmental organization, Employees Performance